Pneumonia in children: Prediction of the temperature response to antibiotic treatment - Nielsen, Hans Erik; Hilden, Jørgen; Gheshlagh, Bijan; Pressler, Tacjana (Journal of Pediatric Infectious Diseases, 2006)
The aim of this study is to establish criteria for distinguishing between antibiotic-sensitive and insensitive pneumonia, from data available at the moment of deciding which treatment to give. Retrospective chart review of 169 consecutive children, aged 1-16 years, admitted to hospital with X-ray-verified pneumonia and treated with intravenous antibiotics, 89% with penicillin (because resistance of pneumococci and of Haemophilus influenzae to penicillin is practically non-existent in Denmark). The temperature response to intravenous antibiotic treatment, as we define it rigorously, was the response variable. Its dependence on the clinical, laboratory and radiological variables available at the moment of diagnosis was analyzed by multiple regression analysis. From the regression model, we derived a rule for predicting the effect of antibiotic treatment on the temperature response. We identified a number of variables that independently predicted rapid resolution of the fever: young age; several days of disease before admission; oral administration of antibiotics before admission; high initial temperature; high white blood cell count; absence of wheezing and of atelectasis; the presence of a sharply delineated and/or spherical lung infiltrate; and a general appearance of being ill, but only in the absence of chest wall retractions. The resulting prediction rule explained less than 50% of the response variability. From the data available at the moment of deciding about treatment for pneumonia, we have identified the parameters that predicted temperature response to antibiotic treatment, but the prediction rule was too imprecise to be clinically useful, i.e., it could not distinguish between those children who would benefit from antibiotic treatment, and those who would not.
Keywords: Pneumonia; treatment; antibiotic; child; fever